Development of project-based learning activities in social studies for grade 4 primary school students - Janthamad, Amarin; Suikraduang, Arun (Journal for Developing the Social and Community, 2026)
Background and Aims: Current teaching methods largely remain lecture-based, confined to classrooms, and lack processes that foster critical thinking skills. Project-based learning, on the other hand, provides students with the opportunity to determine their own learning objectives based on their interests, develop planning skills, systematic execution, implementation, and self-directed learning conclusions. This leads to continuous and sustainable learning. This research aims to: 1) develop project-based learning activities that meet the 80/80 effectiveness criterion; 2) compare pre-test and post-test academic achievement; and 3) study student satisfaction with project-based learning activities in economics. Methodology: This research studied the effects of developing project-based learning activities. The sample consisted of 20 students from Grade 4/1 at Wittayalai Demonstration School, Phanom Phrai District, Roi Et Province, during the first semester of the 2024 academic year, selected using cluster random sampling. The research instruments were: 1) Seven lesson plans totaling 16 hours; 2) A pre- and post-test of achievement consisting of 30 multiple-choice questions with four options; and 3) A questionnaire on student satisfaction with project-based learning, using a 5-level rating scale with 15 items. Results: The findings indicated that: 1) The project-based learning activities in economics for fourth-grade students were effective (E1/E2) with scores of 83.67/87.67, exceeding the set criteria of 80/80. 2) Fourth-grade students who participated in the project-based learning activities showed significantly higher post-test scores compared to pre-test scores at the .05 statistical significance level. 3) Fourth-grade students demonstrated a high level of satisfaction with the project-based learning activities, with an overall average score of 4.49. Conclusion: Developing effective project-based learning activities for Grade 4 Economics students that can be appropriately applied to develop students in higher grades.